Understanding geology through maps - Borradaile, Graham (Elsevier, 2014)
Understanding Geology through Maps guides young professional geologists and students alike in understanding and interpreting the world’s dynamic and varying geological landscapes through the liberal use of visual aids including figures, maps, and diagrams. This highly visual reference introduces the skills of interpreting a geological map and relating it to the morphology of the most important types of geological structure. Thoroughly revised, and with more international examples, it is ideal for use by students with a minimum of tutorial supervision. Maps of geological structures provide all of the realism of a survey map without the huge amount of data often present, so readers can develop or hone their skills without becoming overwhelmed or confused. In particular, emphasis is placed throughout on developing the skill of three-dimensional visualization so important to geologists. -- Provided by publisher.